BAITUL MAL AS A SOLUTION OF DISPUTES OVER INHERITANCES OF HEIRS WITHOUT HEIR - Haeratun; Gumbira, Seno Wibowo; Apriandhini, Megafury (Moestopo International Review on Social, Humanities, and Sciences, 2025)
This article aims to explore the process of economic development through Baitul Mal as a solution for resolving property disputes inherited from deceased individuals who have no heirs in Indonesia. The methodology of this article employs doctrinal or normative legal research, utilizing statutory, conceptual, and comparative approaches. The discussion results indicate that Baitul Mal can serve as a solution in inheritance cases where the deceased does not leave behind any heirs, as well as the allocation of the Baitul Mal portion, which needs to be supported by additional rules. These rules will function as a legal umbrella and a basis for implementation at the national level. Furthermore, positive regulations must always incorporate relevant legal provisions, considering the importance of the principle of legality in decision-making. In conclusion, with a clear legal framework in place, Baitul Mal can significantly contribute to the economic development of the community and the effective management of inherited property.